"A Divine Kind of Rhetoric": Rhetorical Strategy and Spirit-Wrought Sincerity in English Puritan Writing. (December 2017) - Parry, David
In their endeavors to persuade their readers and hearers to conversion and godly living, Puritan writers and preachers in early modern England make use of the three modes of persuasion identified by Aristotle: logos (appeal to rational argument), pathos (appeal to emotion), and ethos (appeal to the perceived credibility of the speaker). Although deploying rhetorical techniques, Puritan writers seek to manifest a Spirit-wrought sincerity, understood as earnest expression flowing from doctrinal conviction, inward spiritual experience, and a heartfelt desire to persuade others. This article explores these dynamics in the works of William Perkins, Richard Sibbes, Richard Baxter, and John Bunyan.